If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 180 + -1x = 46(90 + -1x) 180 + -1x = (90 * 46 + -1x * 46) 180 + -1x = (4140 + -46x) Solving 180 + -1x = 4140 + -46x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '46x' to each side of the equation. 180 + -1x + 46x = 4140 + -46x + 46x Combine like terms: -1x + 46x = 45x 180 + 45x = 4140 + -46x + 46x Combine like terms: -46x + 46x = 0 180 + 45x = 4140 + 0 180 + 45x = 4140 Add '-180' to each side of the equation. 180 + -180 + 45x = 4140 + -180 Combine like terms: 180 + -180 = 0 0 + 45x = 4140 + -180 45x = 4140 + -180 Combine like terms: 4140 + -180 = 3960 45x = 3960 Divide each side by '45'. x = 88 Simplifying x = 88
| 39=84w+39 | | 3(f-8)=33 | | 2x-5=x+9+5 | | -5+4(3-n)= | | y=ln(5x^3) | | 8d^2+30d+25=0 | | -3x+-10x-14=-12 | | (3n+6)(n-2)=0 | | 5-6=3.75 | | 2.8+7=4.8+89 | | 3x=9x-10 | | 42=3y+9 | | 7(-5x+3)=126 | | 7m+4(m-8)= | | log(x^5)-log(x^2)=3 | | -10(s+2)=48 | | 6(2x+4)=25x+250 | | A^2+4a=o | | 0.1(x-7)=3.5 | | y+(-10)=-2(x-5) | | p=6x+2 | | p=6x+1 | | 6789=4 | | -3x+6=x^2+8x+16 | | 0.4x-0.5(2x+3)=0.7(x+3) | | -(2x-4)-(8x-5)+14=-10x(x-1)-(5x+10)+3 | | lnx^5-lnx^2=3 | | P+13=-42 | | 5s+8=48 | | 5x+14=-91-10 | | 5(2x-9)+7x= | | 3p+2p+4y+5y= |